2016
DOI: 10.1038/srep35969
|View full text |Cite
|
Sign up to set email alerts
|

NOGO-A/RTN4A and NOGO-B/RTN4B are simultaneously expressed in epithelial, fibroblast and neuronal cells and maintain ER morphology

Abstract: Reticulons (RTNs) are a large family of membrane associated proteins with various functions. NOGO-A/RTN4A has a well-known function in limiting neurite outgrowth and restricting the plasticity of the mammalian central nervous system. On the other hand, Reticulon 4 proteins were shown to be involved in forming and maintaining endoplasmic reticulum (ER) tubules. Using comparative transcriptome analysis and qPCR, we show here that NOGO-B/RTN4B and NOGO-A/RTN4A are simultaneously expressed in cultured epithelial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 53 publications
(81 reference statements)
5
34
0
Order By: Relevance
“…Apart from the nervous system, Nogo-A was shown to be expressed in the heart tissue, testis and liver, although in the latter the signal was considered unspecific[42]. Furthermore, a recent study by Ramo et al[43] has reported that Nogo-A and Nogo-B are simultaneously expressed in human hepatoma, fibroblast and neuronal cells, concluding than none of the isoforms should be considered a cell type specific isoform and revealed a wider range of functions for Nogo-A outside the nervous system. Another study addressing the expression of Nogo-A in the liver was performed by Hao et al[24], where the authors reported that Nogo-A was highly expressed in four liver cancer cell lines in vitro and the depletion of Nogo-A protein suppressed cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the nervous system, Nogo-A was shown to be expressed in the heart tissue, testis and liver, although in the latter the signal was considered unspecific[42]. Furthermore, a recent study by Ramo et al[43] has reported that Nogo-A and Nogo-B are simultaneously expressed in human hepatoma, fibroblast and neuronal cells, concluding than none of the isoforms should be considered a cell type specific isoform and revealed a wider range of functions for Nogo-A outside the nervous system. Another study addressing the expression of Nogo-A in the liver was performed by Hao et al[24], where the authors reported that Nogo-A was highly expressed in four liver cancer cell lines in vitro and the depletion of Nogo-A protein suppressed cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification was performed with Image Studio software (Li-COR). The antibody against RTN4A and RTN4B recognized only a band of about 50 kDa, indicating that the detected protein was RTN4B (49), and the result was confirmed using sheep polyclonal antibody against RTN4B (MRC-PPU Reagents).…”
Section: Discussionmentioning
confidence: 73%
“…To further examine ER distribution, two additional markers for ER were included. CLIMP-63 (cytoskeleton-linking membrane protein 63), also known as CKAP-4 (cytoskeleton-associated protein 4), is predominantly found in ER sheets (48), and reticulon 4B (RTN4B), also known as neurite outgrowth inhibitor B (Nogo-B), localizes to ER tubules and sheet edges (49). CLIMP-63 showed a distribution similar to that of calnexin, although an additional band was detected in fr.…”
Section: Isolated Sfv Rcs Are Stablementioning
confidence: 99%
“…They are known to be involved in forming and maintaining ER tubules as their over‐expression alters the balance strongly towards tubules and causes the deformation of the cell shape. On the contrary, depletion of RTN4 proteins induces formation of large peripheral ER sheets . Therefore, it is plausible to suggest that functional depletion of reticulons from the ER in aggregate‐containing cells can affect ER structure and other aspects of cellular physiology where their functions are essential.…”
Section: Discussionmentioning
confidence: 99%